2018
DOI: 10.1007/s00420-018-1376-6
|View full text |Cite
|
Sign up to set email alerts
|

Heatwave and work-related injuries and illnesses in Adelaide, Australia: a case-crossover analysis using the Excess Heat Factor (EHF) as a universal heatwave index

Abstract: Heatwave and work-related injuries and illnesses in Adelaide, Australia: a casecrossover analysis using the Excess Heat Factor (EHF) as a universal heatwave index

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Firstly, it should be stressed that weather conditions such as radiant heat, air humidity, wind speed and solar irradiation, in a mountainous region such as the Autonomous Province of Trento, air humidity and solar irradiation may strikingly fluctuate over a restricted area because of the altitude 3,29,[43][44][45] . In other terms, whereas an assessment at municipality level may guarantee a sufficient detail for air temperature, in the settings of our survey it might be not so accurate for other factors 41,[51][52][53][55][56] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Firstly, it should be stressed that weather conditions such as radiant heat, air humidity, wind speed and solar irradiation, in a mountainous region such as the Autonomous Province of Trento, air humidity and solar irradiation may strikingly fluctuate over a restricted area because of the altitude 3,29,[43][44][45] . In other terms, whereas an assessment at municipality level may guarantee a sufficient detail for air temperature, in the settings of our survey it might be not so accurate for other factors 41,[51][52][53][55][56] .…”
Section: Discussionmentioning
confidence: 89%
“…Currently, there is no universal definition of a HW, although most studies have defined HW as a combination of duration (e.g. 3 or more days) and intensity (either as Tmax or average daily temperatures) [52][53] . In order to more easily compare our estimated with previous studies on HWs, an HW event was defined by 3 or more consecutive days having Tmax ≥ 35°C 30,35,36,43) .…”
mentioning
confidence: 99%
“…Occupational health impacts of heatwaves are of economic consequence, where work-related ambulance call outs and compensation claims increased during heatwave events [45,46]. It is identified that the impact of delays and other implications with regard to public transport could greatly impact an individual who relies on this service to fulfil activities that allow them to have access to such necessities as critical medical assistance and medicine [47].…”
Section: Health Sectormentioning
confidence: 99%
“…It is becoming widely recognized that occupational health and safety (OHS) and productivity can be compromised in hot conditions, with several studies reporting on the phenomenon in Canada [1][2][3], the United States of America [4,5], Europe [6,7], Asia [8,9] and Australia [10][11][12][13][14][15][16]. As global temperatures rise and extreme temperatures become more common, prevention measures in workplaces will be essential.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant literature in this area contains mostly quantitative research, characterizing the positive association between high-temperature environments and increased occupational incidents. Studies have involved the analysis of large datasets of occupational health outcomes data, providing valuable evidence on the epidemiology of workplace heat injuries and vulnerable workers [11,13,21,22]. Additionally, worker surveys and field studies have been conducted to elucidate the phenomenon of heat-related incidents in the workplace [19,23,24].…”
Section: Introductionmentioning
confidence: 99%